Integrating Howard Gardner’s Multiple Intelligences in Islamic Education: A Systematic Review of Indonesian Practices - Mahmud, Salami; Musfirah, AM Riska; Marlina, Cut Nyak; Fitria, Syiva; Bujangga, Hendriyanto; Pranajaya, Syatria Adymas; Alfiyanto, Afif (Jurnal Ilmiah Peuradeun, 2024)
This study aimed to collect and analyze articles related to Howard Gardner’s Multiple Intelligences theory and its implementation in Islamic education in Indonesia, as well as to identify research gaps. The method used was a Systematic Literature Review (SLR) with meta-synthesis data analysis techniques. The selected articles were published between 2016 and 2024 and chosen as the subjects of the study. These articles were gathered through search engines such as Google Scholar, Scopus.com, and Elicit.ai. The data analysis techniques employed were both quantitative and qualitative. The analysis results indicated that the implementation of Multiple Intelligences in Islamic Religious Education (PAI) teaching successfully improved student achievement and encourages teachers to teach creatively, using methods such as demonstrations, role-playing, the use of ICT, outdoor learning, and student motivation. Additionally, this implementation fosters critical thinking, problem-solving learning, creative thinking, and communicative learning. The implementation of Multiple Intelligences in PAI also aligned with the concept of fitrah. Further research is recommended to broadly review the implementation of Multiple Intelligences in Islamic education.